Assessment of risk factors associated with anemia among pregnant women attending the obstetrics and gynecology department in a tertiary care hospital, Prakasam District, Andhra Pradesh, India - Venkata Swarajya Lakshmi A; Anamula Sreedevi; Venkata Srinivas Rao; Krishna Chaitanya Botsa (Asian Journal of Medical Sciences, 2024)
Background: Anemia in pregnancy is a pervasive health issue, particularly in developing countries. Aims and Objectives: This study aims to assess various socio-demographic factors, nutritional intake, and other risk factors contributing to anemia among pregnant women attending a tertiary care hospital in Prakasam District, Andhra Pradesh, India. Materials and Methods: A cross-sectional study was conducted involving 160 pregnant women. Data were collected on socio-demographic factors (family type, religion, caste, residence, education, socio-economic status, age, occupation), anemia prevalence, antenatal care, birth spacing, nutritional intake (caloric, protein, and iron), and gravida status. Chi-square tests were used for statistical analysis to determine associations between anemia and various risk factors. Results: The study revealed a high prevalence of moderate anemia (74.4%) among the participants. Most women were from nuclear families (75%), lived in rural areas (89.4%), and were predominantly homemakers (83.1%) in the age group of 21–30 years. Nutritional analysis showed 74.6% of women had a calorie intake below 2000 K. Cal/day, 64.7% had a protein intake below 50 g/day, and 87.5% had an iron intake below 20 mg/day. A significant association was found between anemia and factors such as caloric intake (χ²=10.6654, P=0.001092), gravidity (χ²=7.0278, P=0.008025), and iron intake (χ²=27.277, P<0.00001), but not with protein intake (χ²=3.7547, P=0.052658). Conclusion: The study highlights a high prevalence of anemia among pregnant women in the Prakasam District, primarily associated with inadequate caloric and iron intake and increased gravidity. These findings emphasize the need for enhanced nutritional counseling and healthcare interventions focusing on diet and family planning for pregnant women in this region.